0190 Use of eye-tracking technology to identify performance metrics in simulated anaesthetic critical incidents: A known groups pilot study. (2nd November 2015) - Wright, David; Yusaf, Mamoon; Purva, Makani
Abstract : Background: Eye-tracking is a behavioural analysis tool which may reveal insights inaccessible to the traditional observer. Established in industry, medical applications remain relatively unexplored. We tested feasibility using ambulant subjects, in a simulated operating theatre. We also attempted to validate the technique by comparing the performance of junior and senior anaesthetists. A fixation duration of ≥200 ms allows recognition and higher cortical processing of visual targets. 1 This provides a unique ability to examine disparities between problem recognition and action. Methodology: Ethical approval was obtained. 7 junior and 7 senior anaesthetists undertook a standardised simulated difficult airway scenario. All wore eye-tracking glasses (Ergoneers TM ). 2 monitoring changes (88% desaturation and ventricular tachycardia) were introduced at set times. Monitor SpO2 and ECG traces were defined as 'areas of interest' (AOI). Primary endpoints were time to first fixation (TFF) on AOI following change, and time to act (TTA). Post scenario questionnaires assessed user acceptability. Parametric data was compared using an unpaired t -test and non-parametric data using the Mann-Whitney U test. Results: Mean TFF(s) was less for seniors than juniors, for SpO2 (12.0 vs 29.5, p = 0.05) and ECG (4.1 vs 8.9, p = 0.11). TTA was less for seniors for SpO2 (15.4 vs 53.3, p = 0.02) and ECG (12.9 vs 50.0, p = 0.02). TFF/TTA interval was also less for seniors (SpO2 : 21.1 vs 41, p = 0.07. ECG: 8.7 vs 41.2, p = 0.04). 86% of candidates stated the glasses had no impact on their normal behaviour. Conclusions: Eye-tracking is acceptable for users and deliverable in a dynamic, simulated environment. It is a valid tool to discriminate certain aspects of performance. A prolonged recognition/action interval in juniors, provides a new insight into critical incident behaviour. It may reflect less efficient clinical interpretation, decision-making and action planning. Further scrutiny of this recognition/action phase, may facilitate approaches to improve response times in critical incidents. Reference: Salvucci DD, Goldberg JH. Identifying fixations and saccades in eye-tracking protocols. ETRA 2000: Proceedings of the 2000 symposium on eye-tracking research and applications. New York: ACM, 2000: 71–78